The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/mej.0000000000000263
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nasogastric tubes to enable differentiation between upper and lower gastrointestinal bleeding in unselected patients with melena

Abstract: Gastrointestinal (GI) bleeding is a common surgical problem. The aim of this study was to evaluate how insertion of the nasogastric tube may enable differentiation between upper and lower GI bleeding in patients with melena. A retrospective study involving patients admitted to our surgery division with a melena was carried out between the years 2010 and 2012. A total of 386 patients were included in the study. Of these, 279 (72.2%) patients had negative nasogastric aspirate. The sensitivity of examination of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Only a few patients received nasogastric tubes (10%). Several studies indicated that nasogastric tube placement does not confirm the upper origin of a gastrointestinal bleeding [ 26 , 27 ] and recommendations remain unclear on this topic. Erythromycin perfusion before endoscopy is rarely used [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few patients received nasogastric tubes (10%). Several studies indicated that nasogastric tube placement does not confirm the upper origin of a gastrointestinal bleeding [ 26 , 27 ] and recommendations remain unclear on this topic. Erythromycin perfusion before endoscopy is rarely used [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective study and a review both concluded that nasogastric tube (NGT) aspiration does not differentiate upper from lower GI bleeding in patients with melena [73,74]. Moreover, a randomized, single-blind, noninferiority study comparing NGT placement (with aspiration and lavage) to no NGT placement (n = 140 in each arm), failed to show that NGT aspiration could accurately predict the presence of a high risk lesion requiring endoscopic therapy (39 % vs. 38 %, respectively) [75].…”
Section: Nasogastric/orogastric Tube Aspiration and Lavagementioning
confidence: 99%
“…Nasogastric aspirate has very poor sensitivity to establish an upper GI source of bleeding. In a retrospective cohort of patients with melena undergoing nasogastric aspirate, the sensitivity of nasogastric aspirate to establish an upper GI tract of bleeding was only 28%, and the negative predictive value was <1% (65). Finally, a systematic review was performed to assess the diagnostic precision of the BUN-to-Cr ratio and nasogastric aspiration in patients with GIB without hematemesis.…”
Section: Initial Managementmentioning
confidence: 99%